PENDAMPINGAN PEMANFAATAN JAHE DAN BUNGA TELANG SEBAGAI MINUMAN SERBUK FUNGSIONAL DI DESA ULAK KERBAU BARU TANJUNG RAJA - Agustiarini, Vitri; Hasanudin; Hendri, Muhammad; Said, Muhammad (Jurnal Abdi Insani, 2024)
Ginger and butterfly pea flowers are often found in Ulak Kerbau Baru Tanjung Raja Village. Ginger has benefits as an antioxidant, antiemetic, and anti-inflammatory, while butterfly pea flowers have antioxidant, anticancer, antitussive, and allergic properties. Ginger and butterfly pea flowers have many health benefits, which can be developed into functional powdered drinks. This community service aims to increase knowledge, people's understanding, and skills in utilizing ginger and butterfly pea flowers in functional drink powder products that are good quality and beneficial for health. Activity stages include preparation, implementation, and evaluation stages. The preparation stage begins with observation, discussion of activity program preparation, creation of materials, and pretest-posttest questions. The implementation stage starts with the opening and introduction of the Community Service team and the provision of materials and direct practice. The community service activities were well received, and the community's enthusiasm was very high. In the activities, there was an increase in the community's knowledge and understanding of ginger and butterfly pea flowers. The increase was measured by looking at the pretest (71.8) and posttest (85) scores. Community service participants said that this activity was beneficial and could create an idea for making innovative household products by using plants around the house as products that have health benefits. This community service also improves skills in managing ginger and butterfly pea flowers as functional powdered drinks of good quality. Excellent and beneficial for health. This community service activity can increase the community's knowledge, understanding, and skills in utilizing ginger and butterfly pea flowers in functional powdered drink products.